Development of Student Creativity Trough Innovation Training in Making Soap from Teh-tehan Leaves - YULIANTI, EMA; Oktaviani, Devita; Gian Albana, Meylla; Ambar Wati, Retno; Khofifah Aprini, Dina (JOURNAL INCLUSIVE SOCIETY COMMUNITY SERVIES, 2024)
There are still many students who do not understand the benefits of the content of the-tehan leaves. Most of these plants are only used as natural fences. Even though this leaf has a lot of content that is beneficial for the skin. One innovation that can be developed from these leaves is as a soap base. With the aim of conveying knowledge and skills in making the-tehan leaf soap, which has environmental conservation benefits and reduces the use of harmful commercial soap. The implementation method used is a workshop and direct assistance by Management students of class A2 semester 3 in December 2023. Thus, the trainees can easily understand how to make bath soap using teh-tehan leaves.